The The Impact of Profit-Sharing and Sale-Based Financing on Islamic Bank Stability - Pramesti, Cindy Astuti; Ika Khusnia Anggraini (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
This study analyzes The Effects of Profit Sharing-Based Financing and Trade on the Stability of islamic banks in Indonesia. Bank stability is measured using Return On Aset (ROA) and Capital Adequancy Ratio (CAR) processes. The aim is to analyze the type of financing that contributes the most to the stability of islamic banks. This study uses quantitative methods with Vector Autoregression time series regression analysis on monthly data from January 2016 - June 2023 that obtained from Otoritas Jasa Keuangan (OJK) Islamic Banking Statistics. The results showed that profit sharing financing has a significant positive effect in the short and long term, while trade financing has a significant negative impact in the short term but does not significant effect in the long term on the stability of islamic banks. Based on these findings, it can be concluded that the stability of islamic banks is highly vulnerable to changes in profit sharing financing.